Tuberculosis screening in immigrants from high‐prevalence countries: Interview first or chest radiograph first? A pro/con debate. Issue 3 (21st March 2013) - Mor, Zohar; Leventhal, Alex; Diacon, Andreas H.; Finger, Rebekka; Schoch, Otto D.
Abstract Immigration from high tuberculosis (TB) prevalence countries has a substantial impact on the epidemiology of TB in receiving countries with low TB incidence. Cross‐border migration offers an ideal opportunity for active case finding that will result in a lower caseload in the host country and a reduced spread of disease to both the indigenous and migrant populations. Screening strategies can start 'offshore', thereby indirectly assisting and empowering public health systems in the source countries, or be performed at ports of entry with or without long‐term engagement of 'onshore' facilities and systems to provide either preventive therapy or surveillance for reactivation of latent TB. The chest radiograph seems to be playing a key role in this process, but questions remain regarding when, where and in whom radiographs are best done for optimal yield and cost‐effectiveness, and with what other tests they might best be combined to further increase the usefulness of transborder TB control.